The Impact of Leaf-Eating Caterpillars (Heortia vitessoides) Infestation on Agar Trees in Carita Forest Research Station, Province of Banten - Kuntadi; R.S.B. Irianto (Foresty Faculty of Hasanuddin University, 2018)
The gregarious caterpillars of Heortia vitessoides Moore is a major defoliator of agar trees. The pest seriously threatens the existing agar tree plantation that has been widely cultivated in the community. Pest attacks began to occur in Indonesia since 2005, resulting in the damage and death of agar tree plants in various regions.To determine the impact of pest attack, a study was conducted through periodic monitoring at agar plantation in Carita Forest Research Station (CFRS), Banten Province, from April 2012 to March 2015. Monitoring was conducted in three plots of agar plantations. Each plot consists of six permanent subplots and in each subplot 15 samples of agar tree were randomly choosen. Data were collected and analyzed on monthly basis according to the intensity of defoliation and the mortality of agar trees. Defoliation intensity was determined by the percentage number of trees suffering defoliation in four damage categories, i.e.: light (10-25%), moderate (25-50%), heavy (50-75%), and severe (75-100%). Tree mortality was calculated as the annual percentage of dead trees. The study showed that the defoliation occurred throughout the year in varying degrees of damage. The monthly percentage of defoliated trees is about 30-70% annualy. The high percentage of tree defoliation mainly occurs during dry and early rainy season (June-December). Higher percentage of heavy and severe defoliations were found mostly at seedling. Repeated heavy defoliation causes stunted growth and tree mortality. Early monitoring and control of pests are very important to be done regularly to prevent the damage wider and heavier.